The temporal evolution of the swell and magmatic fluxes along the Louisville hotspot - Smith, Madison Nichole (Kansas State University, 2021)
The interaction of an ascending mantle plume and a moving lithosphere produces two main surface observations: a volcanic chain and swell. The study of the temporal evolution of the magmatic flux, Qv, associated with the volume of magmatic material, and the buoyancy flux, Qs, associated with the swell, provides important information on plume phenomenology, plume temporal evolution, and its interactions with the large-scale mantle flow and the drifting lithosphere. This study focuses on the temporal evolution of the Louisville hotspot. We utilize the MiFil filtering method to separate the swell and magmatic components. We translate a sliding box along the track to compute the temporal evolution of Qs and Qv. For the past ~35 m.y. Louisville’s fluxes have been increasing, indicating an increase in hotspots activity which contradicts previous reports about its decline. This could be caused by variations in the degree of melting, an increase in the plume temperatures, or movement of a deep mantle source. Peaks in both fluxes are found at 2, 12, and 23 Ma along the Louisville seamount chain. Such variations, with a 10-20 m.y. periodicity have been reported for the Hawai’i, Walvis, and St. Helena chains. They may be induced by the tilt of the plume conduit. Variations on a scale of 5 m.y. are identified along the Louisville chain, and have also been reported on St. Helena, Walvis, and Hawai’i. They may be the result of solitary waves that form within the plume conduit after mantle motions have deformed it, allowing instabilities to form and increase plume activity. We find the buoyancy flux, B, associated with the Louisville chain to be 0.65 Mg s⁻¹, similar to the value reported by King and Adam (2004), which is consistent with a shallow plume origin.
Keywords: Hotspot; Louisville; Swell; Magmatic; Flux; Activity